Chlorophyll dephytylation in chlorophyll metabolism: a simple reaction catalyzed by various enzymes. (January 2021) - Lin, Yao-Pin; Charng, Yee-yung
Abstract: Chlorophyll (Chl) is composed of a tetrapyrrole ring and a phytol tail, which facilitate light energy absorbance and assembly with photosynthetic protein complexes, respectively. Chl dephytylation, the hydrolytic removal of the phytol tail, is considered a pivotal step in diverse physiological processes, such as Chl salvage during repair of the photosystem, the Chl cycle in the adjustment of antenna size, and Chl breakdown in leaf senescence and fruit maturation. Moreover, phytol is a component of the tocopherols, a major form of vitamin E that is essential in the human diet. This phytol mostly comes from Chl hydrolysis. However, the authentic enzyme responsible for Chl dephytylation has proved elusive. CHLOROPHYLLASE (CLH) which was discovered over a century ago, was the first enzyme found to have dephytylation activity in vitro, but its role in Chl metabolism has been questioned and remains under debate. Recently, novel dephytylases, i.e., PHEOPHYTINASE (PPH) and CHLOROPHYLL DEPHYTYLASE1 (CLD1) have emerged from genetic studies, indicating that dephytylation in Chl catabolism involves different players and is more complicated than previously thought. Based on sequence homology, substrate specificity, and subcellular localization, CLH, PPH, and CLD1 belong to different types of dephytylase, which prompted us to re-examine the dilemmas and missing links that still exist in Chl metabolism. This review thus focuses on the hitherto unanswered questions involving the Chl dephytylation reaction by highlighting relevant literature, updating recent progress, and synthesizing ideas.